MENINGKATKAN PERTUMBUHAN DAN PRODUKSI RUMPUT LAUT Gracilaria gigas DENGAN MODIFIKASI METODE BUDIDAYA DAN SISTEM JARING - Dwi Sunu Widyartini; H. A. Ilalqisny Insan; Warsinah Warsinah (Sainteks, 2012)
Production the Gracilaria. gigas Harv. is cultivation is influenced by cultivation methods and net systems used as well as environment factor. This research aim to know the growth and production of the Gracilaria gigas using different cultivation methods and net systems and also to determimine the different cultivation method and net system which result in the highest growth and G. gigas production in Selok Adipala ocean in Cilacap. This research used an experimental method with Splitplot Design in 3 times replication for each treatment combination. Research result indicate that the different of cultivation methods and net systems yield different seaweed growth and production. The highest growth was yielded from G. gigas use the modification of floathing method with double nets system that is equal to 4.25,00 g/day. G. gigas using the floathing method with apit net system yield that was equal to 1.610,00 g/ m2 of cultivation sea weed on Selok Adipala ocean in Cilacap Keywords: cultivation methods and net systems, Gracilaria gigas, Selok Adipala ocean in Cilacap